Revealing the influence of design and operational parameters on the characteristics of a hydrostatic bearing in aviation gearbox satellites - Nazin, Vladimir (Eastern-European Journal of Enterprise Technologies, 2026)
This study investigates hydrostatic-dynamic processes in the hydrostatic-dynamic bearing of satellites in the aviation gearbox of a turboprop engine. The task addressed is to determine the influence of design parameters of a multi-chamber hydrostatic bearing on its basic characteristics taking into account the pressure of the working fluid and the diameter of the nozzle at the inlet to the bearing chambers. The basic characteristics considered are the bearing capacity, the flow rate of the working fluid, and the power loss due to friction. The basis for defining these characteristics is the pressure distribution function in the working fluid layer. The influence of the working fluid pressure and the diameter of the nozzle at the inlet to the bearing chambers on the basic characteristics of the hydrostatic-dynamic bearing of the satellite of the aviation gearbox has been studied. It has been established that the required bearing capacity for the selected design and adopted dimensions of the hydrostatic-dynamic bearing is provided at a pressure at the inlet to the bearing chambers of approximately 3 MPa. The value of the bearing capacity at a pressure of 3 MPa is 5438 N. The flow rate of the working fluid at this pressure does not exceed 0.0011 m3/s, or 1.1 l/s. The total power losses due to friction and pumping are approximately 6 kW. With an engine power of 1876 kW, the power losses on 4 satellite bearings are approximately 1.28% of the total engine power. The results are obtained with a nozzle diameter at the inlet to the bearing chambers of 2.5 mm. Such a nozzle diameter allows for reliable operation of the hydrostatic-dynamic bearing under various operating modes. The findings show that by selecting the design and operational parameters, the hydrostatic-dynamic bearing provides the necessary bearing capacity of the supports of satellites in aircraft gearboxes. Power losses from the use of hydrostatic bearings in the satellites of the aircraft gearbox practically do not affect the total power of the turboprop engine